Effects of cardiorespiratory fitness and body mass index on cardiometabolic risk factors in schoolchildren - Natália Carvalho Bagatini; Carolina Dertzbocher Feil Pinho; Gabriela Tomedi Leites; Rogério da Cunha Voser; Anelise Reis Gaya; Giovani dos Santos Cunha (BMC, 2023)
Abstract Introduction High levels of physical fitness established during childhood and adolescence have been associated with positive effects on cardiometabolic risk factors (CMRF), which persist into adulthood. Conversely, a sedentary lifestyle, overweight, and obesity during this period are considered public health problems. These conditions tend to worsen in adulthood, increasing the incidence of chronic diseases, deteriorating CMRF, and consequently leading to higher comorbidity and mortality rates. Objective To investigate the effect of cardiorespiratory fitness (CRF) and body mass index (BMI) on CMRF in children and adolescents. Methods The sample consisted of 49 schoolchildren of both sexes aged 10-17 years. Anthropometric assessments, CRF test, muscle strength test, and blood pressure (BP) measurement were conducted. Participants were allocated into groups based on BMI (eutrophic, overweight, obese), and CRF levels (low-fit, normal-fit, and high-fit). Results Obese individuals had lower CRF values compared to the eutrophic and overweight groups. The cardiometabolic risk profile (CMRP) was significantly higher in the obese group compared to the eutrophic group but showed no significant difference compared to the overweight group. The hight-fit group had lower CMRP values compared to the low-fit group. Conclusions Higher BMI and CRF values had negative and positive effects on CMRF and CMRP in schoolchildren, respectively. Overweight or obese schoolchildren with low levels of CRF constitute an unfavourable cardiometabolic risk profile.